2013
DOI: 10.1021/la304954h
|View full text |Cite
|
Sign up to set email alerts
|

C–H Stretch for Probing Kinetics of Self-Assembly into Macromolecular Chiral Structures at Interfaces by Chiral Sum Frequency Generation Spectroscopy

Abstract: Self-assembly of molecules into chiral macromolecular and supramolecular structures at interfaces is important in various fields, such as biomedicine, polymer sciences, material sciences, and supramolecular chemistry. However, probing the kinetics at interfaces remains challenging because it requires a real-time method that has selectivity to both interface and chirality. Here, we introduce an in situ approach of using the C-H stretch as a vibrational probe detected by chiral sum frequency generation spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
90
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(94 citation statements)
references
References 50 publications
3
90
1
Order By: Relevance
“…Chiral SFG has the advantages of being free of spectral background from achiral molecules, including water. 18, 19, 20 Due to the difference in selection rules, 20 the chiral SFG spectrum (Figure 1D) of BslA at the air/water interface is different from the achiral SFG spectrum (Figure 1C). It exhibits only one amide I band at 1639 cm −1 , which is at the high-frequency end of the antiparallel β-sheet B 2 vibrational mode and the low-frequency end of disordered structures.…”
mentioning
confidence: 99%
“…Chiral SFG has the advantages of being free of spectral background from achiral molecules, including water. 18, 19, 20 Due to the difference in selection rules, 20 the chiral SFG spectrum (Figure 1D) of BslA at the air/water interface is different from the achiral SFG spectrum (Figure 1C). It exhibits only one amide I band at 1639 cm −1 , which is at the high-frequency end of the antiparallel β-sheet B 2 vibrational mode and the low-frequency end of disordered structures.…”
mentioning
confidence: 99%
“…Thus, it has become much-used for the study of interfacial proteins 18 38 and has enabled researchers to study these systems in real time and in situ . 19 , 24 , 27 , 31 33 , 39 44 In particular, many recent experiments have focused on the amide I (primarily CO-stretch) mode, which has also been extensively used for linear and 2D IR studies. 11 , 13 , 45 51 This mode is particularly attractive for proteins because it exhibits distinct spectral features for different secondary structures.…”
Section: Introductionmentioning
confidence: 99%
“…Among these works, a surface‐specific vibrational technique, sum frequency generation (SFG) spectroscopy, has been used successfully to minimize the interference from water bulk, allowing detailed molecular studies of structures, kinetics, and interactions of proteins at interfaces . Nonetheless, most of these previous studies focused on the amide I and C‐H stretching regions . A few research groups have recently observed achiral SFG signals of N‐H stretching at ~3300 cm ‐1 from peptides and proteins at interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Nonetheless, most of these previous studies focused on the amide I and C-H stretching regions. [9][10][11] A few research groups have recently observed achiral SFG signals of N-H stretching at~3300 cm -1 from peptides and proteins at interfaces. For example, Somorjai and coworkers tentatively discussed the assignment of thẽ 3300-cm -1 peak from the peptide LK 7 β (LKLKLKL) in the achiral SFG to be the N-H stretch from the backbone.…”
Section: Introductionmentioning
confidence: 99%